Day time variations of zooplankton species composition: observations from the wetlands of Assam, India - Das,Papia (2020)
Abstract: Aim An attempt to justify the variations in the species composition of zooplankton over the day time period was made using the freshwater lakes of Assam, India, as a model study area. Methods The water bodies were sampled using a conical plankton net five times between 6 am and 6 pm in a day during July 2014. Apart from diversity analysis (SHE analysis), discriminant function analysis and a regression tree were built to justify the variations in the zooplankton species composition in the different time periods in a day. Results Repeated sampling during day time indicated the presence of 34 zooplankton species with varied composition over the different time periods. The species richness and abundance of Copepoda, Cladocera and Rotifer differed significantly revealed through the ANOVA (for rotifers – F4, 170 = 28.792; for cladocerans – F4, 170 = 16.343; for copepods - F4, 170 = 9.027). Apparently, the rotifer and copepod abundance was prominent during the early (6am) and late time (6pm) periods of a day while the cladoceran abundance was significant during the middle time periods (12 noon to 3pm) of a day. Variations in the relative abundance of the zooplankton species within a day were sufficient to discriminate the time periods significantly. The regression tree indicated the rotifer abundance (node 1), followed by the cladoceran and the copepod abundances (node 2). The nodes representing cladocerans explained 30.86% of the data while the copepod explained 69.14% data as a split from the rotifer groups. Conclusions A correspondence of high and low abundances of rotifers and cladocerans was characteristic of the species composition of the zooplankton in the study area. The variations in the species composition suggests that the zooplankton exhibits movements either in horizontal or vertical directions induced by physical and/or biological factors. Further studies may be adopted to elucidate the effects of the predators and environmental variables that shape the community of the zooplankton in shallow tropical lakes.